1995
DOI: 10.1093/oxfordjournals.molbev.a040223
|View full text |Cite
|
Sign up to set email alerts
|

The concerted evolution of 5S ribosomal genes linked to the repeat units of other multigene families.

Abstract: We review all instances in which the nuclear 5S rRNA genes of fungi, protist, nematode, and arthropod species have been reported to be linked to the tandemly repeated units of the rDNA, trans-spliced leader, and histone multigene families. The evolution of these gene arrangements is analyzed by mapping them to independently derived phylogenies. These analyses show that 5S rRNA genes have repeatedly become linked to diverse tandemly repeated gene families and that such linkages have also been subsequently inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 93 publications
1
34
0
Order By: Relevance
“…Additionally, the occurrence of alternate 5S and major rDNA signals on extended chromatin fibers of R. decussatus suggests that these sequences are intercalated. Our results showing the existence of linkage between major and 5S rDNA sequences in R. decussatus but not in its congeneric species, R. philippinarum , or in any of the other species within the subfamily Tapetinae, Polititapes aureus , Venerupis corrugata, and P. rhomboides, support the suggestion that 5S and major rRNA gene linkages have been repeatedly established and lost during the evolution of eukaryotic genomes [1, 2]. These data are also in agreement with previous results reported in a wide analysis of metazoan genomes [32] in which, though 5S rDNA was found to be linked to various noncoding RNA genes in several clades, no evidence of evolutionary-conserved linkage among them was detected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, the occurrence of alternate 5S and major rDNA signals on extended chromatin fibers of R. decussatus suggests that these sequences are intercalated. Our results showing the existence of linkage between major and 5S rDNA sequences in R. decussatus but not in its congeneric species, R. philippinarum , or in any of the other species within the subfamily Tapetinae, Polititapes aureus , Venerupis corrugata, and P. rhomboides, support the suggestion that 5S and major rRNA gene linkages have been repeatedly established and lost during the evolution of eukaryotic genomes [1, 2]. These data are also in agreement with previous results reported in a wide analysis of metazoan genomes [32] in which, though 5S rDNA was found to be linked to various noncoding RNA genes in several clades, no evidence of evolutionary-conserved linkage among them was detected.…”
Section: Discussionsupporting
confidence: 80%
“…Minor rDNA repeats consist of a sequence which codes for the 5S rRNA and a nontranscribed spacer (NTS). Although in most eukaryotes in which the organization of these genes is known the two types of rDNAs are located on different chromosome pairs, an increasing number of studies have reported the existence of clusters of both major and minor rRNA genes mapping to the same chromosomal position in many species [1, 2]. Furthermore, the changes in both number and chromosomal position of the rDNA clusters have helped to solve some uncertainties in the phylogenies of some groups of organisms [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interspersed organization of linker histone genes and 5S rDNA described here is the first report of such an association in a marine organism. Given that 5S rRNA and linker histone genes are transcribed by different RNA polymerases, this linkage does not suppose any obvious functional advantage [36] and may represent another example of the reported invasion of different tandemly repeated gene families by 5S rRNA genes through transposition events [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Aside from RNAP I transcription, RNAP II transcription appears to be widespread in eukaryote rDNA (27, 5155). Furthermore, RNAP III-transcribed 5S rDNA genes are located within the rDNA repeat in several species, including yeast (Figure 1; (56)). Moreover, around thirty s mall i nterspersed n uclear e lement (SINE) retrotransposons that derive from RNAP III-transcribed genes are found scattered throughout the human rDNA intergenic spacer (57).…”
Section: Transcription and Nucleolus Directed Organizationmentioning
confidence: 99%
“…crustaceans, and dinoflagellates), or entirely linearly dispersed ( e.g. Neurospora crassa and Schizosaccharomyces pombe ) (56, 65–70). However, these differences in the linear organization of the 5S genes between species belie commonalities in their spatial localization.…”
Section: The Nucleolus and Rna Polymerase III Decoded Genesmentioning
confidence: 99%